Effect of Yiqihuoxue Formula for the treatment of ischemic stroke: A retrospective study. Issue 49 (4th December 2020) - Ren, Dong-Feng; Wang, Ting; Sun, Guo-Fang; Jiang, Chao
Abstract : Abstract: This retrospective study assessed the feasible effect of Yiqihuoxue Formula (YQHXF) for the treatment of patients with ischemic stroke (IS). A total of 66 patients with IS were included in this retrospective study. All patients received routine treatment, and were divided into two groups: a treatment group (n = 33) and a control group (n = 33). In addition to the routine treatment, all patients in the treatment group also underwent YQHXF treatment. All patients in both groups were treated for a total of 8 weeks. The outcomes were assessed by National Institute of Health Stroke Scale (NIHSS), modified Rankin scale (mRS), Barthel index scale (BIS), stroke-specific quality of life (SS-QOL) scale, and adverse events. All outcomes were measured before and after the treatment. After treatment, patients in the treatment group showed better improvements in NIHSS scale ( P  = .01), mRS ( P  < .01), BIS ( P  = .04), and SS-QOL scale ( P  = .04), than patients in the control group. No treatment-associated adverse events were recorded in this study. The results of this study indicated that YQHXF may benefit for patients with IS.